Class 5 allomorphy in Ciyao - Annindo S. Ngunga (LibraryPress@UF, 1997)
Studies of Ciyao, a Bantu language classified as P.21 by Guthrie [1967-71], agree that there are 18 noun classes, each of which determines a primary prefix on the noun, and concord prefixes on elements that agree with head nouns. Most of the primary prefixes have the shape CV- or N- both in Proto-Bantu and in Ciyao. In contemporary Ciyao, class 5 nouns take a prefix which has two allomorphs, the expected CV- di- alternating with the isolated CVV- dii-, posing the problem of how to explain their source and distribution. The purpose of this paper is to document the realization of Ciyao class 5 in detail, and to demonstrate that the di/dii- alternation is prosodically conditioned.